CULTURAL HERITAGE MAINTENANCE OF RU-KETU TRADITION OF SABU PEOPLE - Erny Selfina Nggala Hambandima; Zuvyati A. Tlonanen; Ifoni Ludji (e-Journal of Linguistics, 2025)
This research describes the Sabu People’s attempts to preserve their tradition, especially the Ru-ketu tradition. This is a descriptive qualitative study. This study gathered data by interviewing as primary data and documentation as secondary data. The descriptive qualitative approach was utilized for data analysis, with stages of finishing the transcription process of interviewing, data analysis, and concluding. Unstructured interviews and documentation were employed as data-gathering instruments. The study’s findings indicate that the Sabu people still maintain the Ru’ketu tradition due to some views (1) as a symbol of kinship and love for family and their birth. (2) Death custom that collects and brings together living people as faces of the departed. (3) As a socio-cultural symbol of the Sabu people that explains the feeling of love for their native land which is considered the center of the world.